Biodegradation of Spilled Diesel Fuel in Agricultural Soil: Effect of Humates, Zeolite, and Bioaugmentation. (8th January 2014) - Kuráň, Pavel; Trögl, Josef; Nováková, Jana; Pilařová, Věra; Dáňová, Petra; Pavlorková, Jana; Kozler, Josef; Novák, František; Popelka, Jan
Abstract : Possible enhancement of biodegradation of petroleum hydrocarbons in agricultural soil after tank truck accident ( 5000 mg/kg dry soil initial concentration) by bioaugmentation of diesel degrading Pseudomonas fluorescens strain and addition of abiotic additives (humates, zeolite) was studied in a 9-month pot experiment. The biodegradation process was followed by means of analytical parameters (hydrocarbon index expressed as content of C10 –C40 aliphatic hydrocarbons, ratio pristane/C17, and total organic carbon content) and characterization of soil microbial community (content of phospholipid fatty acids (PLFA) as an indicator of living microbial biomass, respiration, and dehydrogenase activity). The concentration of petroleum hydrocarbons (C10 –C40 ) was successfully reduced by 60% in all 15 experiment variants. The bioaugmentation resulted in faster hydrocarbon elimination. On the contrary, the addition of humates and zeolite caused only a negligible increase in the degradation rate. These factors, however, affected significantly the amount of PLFA. The humates caused significantly faster increase of the total PLFA suggesting improvement of the soil microenvironment. Zeolite caused significantly slower increase of the total PLFA; nevertheless it aided in homogenization of the soil. Comparison of microbial activities and total PLFA revealed that only a small fraction of autochthonous microbes took part in the biodegradation which confirms that bioaugmentation was the most important treatment.